Simulation in Cleft Surgery - Rami S. Kantar, MD, MPH; Allyson R. Alfonso, BS, BA; Elie P. Ramly, MD; J. Rodrigo Diaz-Siso, MD; Corstiaan C. Breugem, MD, PhD; Roberto L. Flores, MD (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. A number of digital and haptic simulators have been developed to address challenges facing cleft surgery education. However, to date, a comprehensive review of available simulators has yet to be performed. Our goal is to appraise cleft surgery simulators that have been described to date, their role within a simulation-based educational strategy, the costs associated with their use, and data supporting or refuting their utility.